Bronchoscopic balloon dilatation for tuberculosis-associated tracheal stenosis: a two case report and a literature review. Issue 1 (December 2016) - Fang, Yong; You, Xiaofang; Sha, Wei; Xiao, Heping
Abstract Background Bronchoscopic balloon dilatation (BBD) is a common strategy in the treatment of bronchostenosis. However, the longer dilating time in each inflation cycle (approximately 3–5 min) without mechanical ventilation is not possible for the treatment of tracheal stenosis. Case presentation In this study, we reported our experience of BBD with shorter dilating time (10 s or 1 min) and intermittent ventilation for the repair of tuberculous-associated tracheal stenosis in two cases of our hospital. After the surgeries, the physical examinations and pulmonary function were tested. In case 1, the cough and dyspnea syndromes subsided, wheeze and strid or in lungs were remarkably reduced, tracheal lumen was considerably expanded and pulmonary function was improved following the treatment. For the case 2, her chest tightness, shortness of breath symptoms were alleviated after the treatment. The middle and lower trachea stenosis was dilated and patent, but the right main bronchus stenosis was slightly improved. No restenosis occurred in the two patients in 1 year outpatient follow-up. Conclusions These findings suggest that our modification in BBD is safe and effective for treating this patient with tracheal stenosis caused by tuberculosis, but the longer-term effect of the surgery in a large number of patients with longer follow-up remains to be seen.